Soil water phenomena of a shortgrass prairie site - Van Haveren, Bruce P., author; Striffler, William D. (William David), advisor; Klute, Arnold, committee member; Meiman, James R. (James Richard), committee member; Jameson, Donald A., committee member (Colorado State University. Libraries, 1974)
This thesis represents an investigation of soil water recharge and depletion phenomena on a shortgrass prairie site in northeastern Colorado. Soil type, grazing intensity, and various topographic variables were all studied to determine their influence on the soil water balance. The soil water balance was subdivided into three periods: recharge due to snowmelt, recharge due to spring rainfall, and growing season depletion. It was estimated that over 60% of the winter precipitation was lost to a combination of evaposublimation and wind transport of snow; it is highly likely that wind-transported snow accounts for over half of this loss. Despite this loss, approximately 48% of the total soil water recharge received between growing seasons 1970 and 1971 was derived from snowmelt. On some optimum sites snowmelt accounted for over 70% of the total recharge. Of the many topographic variables affecting snow retention on the prairie, slope exposure to prevailing winds appears to be the most important, with leeward slopes trapping considerably more snow than windward slopes. In evaluating position-on-slope, it was found that sites which occupy the middle and lower one-third slope positions are optimum sites for snow accumulation. In addition, this study supports the conclusions of earlier workers, who found that snow retention is directly related to vegetation height. Under the precipitation regime of 1971, soil water recharge by rainfall appeared to be independent of the various soil, grazing, and topographic variables investigated. Thus, it is concluded that the spatial distribution of soil water recharge received between growing seasons on the prairie is largely dependent upon patterns of snow retention and redistribution. Actual evapotranspiration fell below potential evapotranspiration early in the growing season on all sites. Thus, patterns in soil water recharge had an important influence on spatial distribution of seasonal evapotranspiration. This influence apparently overshadowed soil type and grazing intensity effects on soil water depletion. Soil water potential data, obtained with thermocouple psychrometers, substantially supported the idea that the soil water regime on the shortgrass prairie is indeed dry. Soil water potentials at depths above 40 cm in most soils reached the -70 bar limit by the end of July, 1971. These results indicate the potential usefulness of thermocouple psychrometers in field studies of soil-water and soil-plant-water relations.
Keywords: Grassland ecology -- Colorado; Natural history -- Colorado